Duties of The Church Diaconal According to Acts 6:1-7 - Imel Poceratu (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diaconal ministry to those in need is a statement that needs to be proven by conducting a study based on the original manuscripts of the Bible. So to achieve this goal, the author conducts literary research using biblical studies of the New Testament and using a historical-critical approach. As the number of disciples grew, there was one ministry that the apostles neglected, the